Investigation of SnO2 doped Al2O3 thin film via electrospinning with different annealing temperature / Muhammad Nizar Aiman Mohd Zani - Mohd Zani, Muhammad Nizar Aiman (2019)
Tin Oxide (SnO2) is an n type semiconductor with direct band gap of 3.6eV. It is highly conducting, transparent and sensitive to gases. The energy band gap is one of the important parameter of SnO2. This work was to characterize the optical properties of SnO2 with different annealing temperature. The thin films of SnO2 doped with AI2O3 was deposited by electrospinning method on the glass substrates. The thin films were annealed at 100°C, 200°C, 300°C, 400°C, 500°C then the optical and physical were investigated. Structural and morphological analysis were carried out by X-Ray Diffraction (XRD) measurement and Microscope. The optical characteristics were analyzed by UV-Vis Spectrophotometer. As annealing temperature increases, optical transmission increase too, this due to the increase in film homogeneity and degree of crystallinity of the film. The increase the temperature lead to decrease in absorption values.